Efektivitas Terapi Audio Visual (Film Kartun) Terhadap Kecemasan Pada Anak Usia Prasekolah - Sri Ekasaputri; A Arniyanti (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: Anxiety is a subjective experience in the form of uncomfortable feelings that arise from non-specific causes. Pharmacological therapy to reduce anxiety is the administration of anti-anxiety drugs (alprazolam triazolobenzodiazepine) 0.5 mg 3 times a day. One of the distraction techniques that can be used to reduce anxiety in children undergoing nursing actions is the use of audio-visual therapy (cartoon films). Purpose: This study (literature review) was to determine the effectiveness of audio-visual therapy (cartoon films) on anxiety in preschoolers. Methods: This study explores quantitative evidence published in electronic databases such as PubMed, and google scholar. By using a journal search strategy, the final results are 3 articles which are the main references in the preparation of this research. Results: From the three articles reviewed, it can be seen a significant effect in reducing anxiety levels in preschool children after being given audio-visual therapy intervention. Conclusion: That audio-visual therapy (cartoon films) is effective in reducing anxiety levels in children aged 3-6 years